2013
DOI: 10.1177/2167702613484717
|View full text |Cite
|
Sign up to set email alerts
|

A Mood Management Intervention in an Internet Stop Smoking Randomized Controlled Trial Does Not Prevent Depression

Abstract: Smoking and depression are related, and mood management interventions included in smoking cessation interventions can increase smoking abstinence rates. Could a mood management intervention embedded in an Internet-based smoking cessation intervention prevent major depressive episodes? Spanish- and English-speaking smokers (N = 17,430) from 191 countries were randomized to one of four online self-help intervention conditions (two with mood management). We analyzed preventive effects among those participants wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…The authors wondered if smokers at risk for major depressive episodes (defined as having subthreshold levels of major depression symptoms at baseline) who had been randomly assigned to receive the mood management intervention had lower incidence of major depressive episodes at follow up, thus showing a preventive effect. The results showed that the incidence was actually significantly greater for the group assigned to the mood management condition ( 90 ). The authors speculate that being assigned to a mood management intervention when one is not looking for such might make a participant more aware of depressive symptoms, thus increasing their self-report scores at follow-up assessments.…”
Section: Possible Adverse Effects Of Mhd Prevention Imismentioning
confidence: 96%
“…The authors wondered if smokers at risk for major depressive episodes (defined as having subthreshold levels of major depression symptoms at baseline) who had been randomly assigned to receive the mood management intervention had lower incidence of major depressive episodes at follow up, thus showing a preventive effect. The results showed that the incidence was actually significantly greater for the group assigned to the mood management condition ( 90 ). The authors speculate that being assigned to a mood management intervention when one is not looking for such might make a participant more aware of depressive symptoms, thus increasing their self-report scores at follow-up assessments.…”
Section: Possible Adverse Effects Of Mhd Prevention Imismentioning
confidence: 96%
“…Perhaps the most salient ones are the high rates of attrition ( Eysenbach, 2005 , Muñoz et al, 2015 ), lower adherence, and effect sizes that tend to be small to moderate ( Andersson and Cuijpers, 2009 ). There is some emerging evidence that in some circumstances, Internet interventions for depression can produce negative effects ( Schueller et al, 2013 ), but this topic has been has been scarcely explored in the literature ( Rozental et al, 2014 ). Certainly, several of these limitations are not particular to unsupported Internet interventions.…”
Section: Introductionmentioning
confidence: 99%
“…We included an 8-session mood management intervention modeled after face-to-face clinical appointments, and few people actually completed the sessions. In this proposal, we are attempting to be mindful of not limiting our designs using skeuomorphic thinking [ 30 ]. We propose to observe how digital tools are used by the population we are choosing to serve in their day-to-day lives and design our interventions in ways that are likely to fit the behavioral patterns we observe.…”
Section: Introductionmentioning
confidence: 99%